The influence of arabic on persian language and literature - Zhetpisbayeva, K. B. (Journal of Oriental Studies, 2016)
This article discusses the influence of Arabic language on Persian language and literature at different periods of its development. Special attention was given to the analysis of loanwords of Arabic origin and features of using new Arabic loanwords by famous poets of Iran. Also, there was considered peculiarities of the new literary style with the advent of Islam.